2021
DOI: 10.1007/s00248-020-01671-x
|View full text |Cite|
|
Sign up to set email alerts
|

Nitrogen Assimilation Varies Among Clades of Nectar- and Insect-Associated Acinetobacters

Abstract: Floral nectar is commonly colonized by yeasts and bacteria, whose growth largely depends on their capacity to assimilate nutrient resources, withstand high osmotic pressures, and cope with unbalanced carbon-tonitrogen ratios. Although the basis of the ecological success of these microbes in the harsh environment of nectar is still poorly understood, it is reasonable to assume that they are efficient nitrogen scavengers that can consume a wide range of nitrogen sources in nectar. Further, it can be hypothesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 75 publications
1
20
0
Order By: Relevance
“…Although the α-proteobacterial ANPR or Rhizobium is usually known as a nitrogen-fixing bacterium living in symbiosis with legume roots [ 67 ], it has also been detected in insects [ 68 ], where a gene associated to nitrogen fixation was revealed in ants that host Rhizobiales [ 69 ]. The γ-proteobacterial Acinetobacter improves both its host nutrition and defense by scavenging nitrogen [ 70 ], producing cellulase [ 52 ], and resisting and degrading plant defenses, respectively in D. radicum [ 53 ] and in the gypsy moth [ 71 ]. Alkanindiges is not commonly found in insects but was detected in ants [ 72 ] while Cellvibrio was first obtained from field soil in Japan but was also detected in a beetle species [ 73 ]; the latter bacterial genus is known to degrade polysaccharides such as cellulose [ 74 ] which would help the host digesting plant material.…”
Section: Discussionmentioning
confidence: 99%
“…Although the α-proteobacterial ANPR or Rhizobium is usually known as a nitrogen-fixing bacterium living in symbiosis with legume roots [ 67 ], it has also been detected in insects [ 68 ], where a gene associated to nitrogen fixation was revealed in ants that host Rhizobiales [ 69 ]. The γ-proteobacterial Acinetobacter improves both its host nutrition and defense by scavenging nitrogen [ 70 ], producing cellulase [ 52 ], and resisting and degrading plant defenses, respectively in D. radicum [ 53 ] and in the gypsy moth [ 71 ]. Alkanindiges is not commonly found in insects but was detected in ants [ 72 ] while Cellvibrio was first obtained from field soil in Japan but was also detected in a beetle species [ 73 ]; the latter bacterial genus is known to degrade polysaccharides such as cellulose [ 74 ] which would help the host digesting plant material.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas A. nectaris prefers fructose and does not grow well on sucrose and glucose, Metschnikowia is able to hydrolyze sucrose and consume the resulting glucose, enriching the nectar in fructose [32,45]. Likewise, in a recent study it has been found that nectar acinetobacters consume a wide diversity of nitrogen sources, including by-products of yeast metabolism [56]. Such interactions may also explain why A. nectaris was abundantly present in the yeast + bacteria treatment, while it was less abundant when only the bacteria were applied, even though at a double dose was used.…”
Section: Plos Onementioning
confidence: 99%
“…Alternatively, bacterial effects may facilitate yeast growth. 50,59 Though we predict that the observed benefit from pollen is due to the observed increased availability of protein (Figure 4), pollen germination or bursting could also release other components including lipids, sterols, trace elements 3 or growth hormones. 60,61 Additionally, the UP may have been altered in other ways that we were unable to characterize, which may also affect microbial growth.…”
Section: Discussionmentioning
confidence: 96%
“…While pollen benefits the growth of most nectar microbes, 9,10 the results here demonstrate that microbial species differentially induce changes in pollen physiology that affect nutrient release and obtain differential growth benefit from pollen in a habitat that is often nutrient limited. 15,17,50 Acinetobacter's ability to access additional pollen nutrients likely contributes to its ecology. The nectar environment is a highly specialized niche, requiring microbial inhabitants to tolerate high osmolarity, plant secondary metabolites or toxins, reactive oxygen species (ROS), and low nutrient levels-all within an ephemeral habitat.…”
Section: Discussionmentioning
confidence: 99%